PENGARUH REALISTIC MATHEMATICS EDUCATION (RME) BERBASIS MULTISENSORI TERHADAP PEMAHAMAN KONSEP DAN DISPOSISI MATEMATIS SISWA SEKOLAH DASAR - Dessy Trisnawati; Ririn Widiyasari; Viarti Eminita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the effect of Realistic Mathematics Education (RME) with a multisensory approach on conceptual understanding and mathematical disposition among sixth-grade elementary students studying spatial structures (cubes and blocks). Employing a quasi-experimental nonequivalent control group pretest-posttest design, the research involved 74 students from SDN Jatimulya 11 Bekasi (37 experimental group, 37 control group). Instruments included a conceptual understanding test (30 items, reliability α>0.70) and a mathematical disposition questionnaire (30 Likert-scale items), analyzed using descriptive statistics, assumption tests (normality, homogeneity), MANOVA, and independent t-tests. Results revealed that the experimental group's posttest mean for conceptual understanding was 82.84 (SD=8.29), significantly higher than the control group's 68.51 (SD=10.06), while mathematical disposition scores were 119.05 (SD=9.41) versus 102.05 (SD=10.79). MANOVA confirmed a significant multivariate difference (Wilks' Lambda p<0.001), supported by t-tests (p<0.05 for both variables). In conclusion, multisensory RME effectively enhances conceptual understanding and mathematical disposition simultaneously, recommended for elementary mathematics instruction under the Merdeka Curriculum.